Goal Programming Advanced Yield Model by Artificial Intelligence and R Programming - Shalini, K.; Polasi, Sridevi; Kuntal, Ravinder Singh; Vishwanatha, S.; Patil, Vishal (SN computer science, 2024)
A nation’s economic and social progress is strongly influenced by its agricultural sector. Crop distribution, crop combination, and operational activities for crop production are critical decisions that must be made in order to get the best farm outputs. The goal of this work is to develop an optimal crop design using goal programming formulation aimed at achieving higher returns for farmers compared to their current net returns. In this work, LINGO 19.0 and R programming were employed to analyze the data. The same result is shown by both programming models. The result shows that allocating 103.3 acres of land to paddy and wheat gives an income of Rs. 44,79,860 which increases the net profit by 32.8% more than the current farmers’ plan. Similarly, other optimal plan increases the net profit from 5.49 to 20.18%.